2010
DOI: 10.1590/s1516-80342010000400015
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional e desenvolvimento da linguagem em crianças de uma creche pública

Abstract: OBJETIVO: Investigar a associação entre estado nutricional e desenvolvimento da linguagem infantil. MÉTODOS: Participaram do estudo 34 crianças de quatro a seis anos e 11 meses de idade de creches de Belo Horizonte, Minas Gerais. As crianças foram avaliadas quanto ao desenvolvimento da linguagem receptiva e expressiva utilizando-se as tarefas do instrumento de Avaliação de Desenvolvimento de Linguagem (ADL). Para a avaliação nutricional foram utilizados os índices estatura/idade e peso/idade, de acordo com os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
1
8
0
4
Order By: Relevance
“…This finding corroborates other studies conducted in public early childhood education schools [17][18][19][20] , where the percentage of language deficits was found to be around 30%. The relevant literature 21 showed that language disorders are the most frequent issues in the development of preschool-age children.…”
Section: Discussionsupporting
confidence: 92%
“…This finding corroborates other studies conducted in public early childhood education schools [17][18][19][20] , where the percentage of language deficits was found to be around 30%. The relevant literature 21 showed that language disorders are the most frequent issues in the development of preschool-age children.…”
Section: Discussionsupporting
confidence: 92%
“…Musiek e Geurkink (1982) O processamento auditivo pode causar ou estar associado a dificuldades de leitura, escrita, linguagem e aprendizagem. Muitos estudos encontrados na literatura sobre desnutrição relatam alterações de aprendizagem e memória (Frota et al, 2009), linguagem (Santos et al, 2010) e fracasso escolar (Turini et al, 1978) infecções, dentre elas a otite, que pode ocasionar um prejuízo na acuidade auditiva e, consequentemente, no processamento da informação acústica (Barros et al, 1995e Lasisi et al, 2007e Elemraid et al, 2011.…”
Section: Parte II -Discussão Sobre a Caracterização Dos Resultados Daunclassified
“…The specific nutrient deficiencies may result in decreased ability to pay attention and affect problem-solving skills (3) . There is an association between the child's alimentary insufficiency and growth, development and behavioral or academic function (3,(5)(6)(7) . Depending on the duration and intensity of the nutritional deficiency, neural functions such as cognition, consciousness, emotion, learning, memory, motivation and anxiety can be affected (8,9) .…”
Section: Introductionmentioning
confidence: 99%